Combination of secondary intention healing and primary closure to reconstruct large facial defects: minireview - Arif, Nawa; Baumann, Lara; Felcht, Moritz (Journal der Deutschen Dermatologischen Gesellschaft, 2024)
Secondary intention healing has been a well-established method to close wounds for more than 200 years. Indeed, it represents the easiest technique in the ladder of plastic reconstruction. Primary wound closure (side-to-side closure, direct wound closure) is the second easiest method. The combination of these two techniques is already an integral aspect of specific surgical procedures, e.g. the reconstruction of the donor site of a paramedian forehead flap. This minireview will show that the combination is also a suitable alternative to classic flaps in reconstruction of different aesthetic subunits of the face. These are the scalp, the lateral cheek, the upper nasal sidewall/medial canthus and the retroauricular region. The advantages and disadvantages will be discussed and illustrated with clinical examples.
Gesehen am 04.11.2024
Erstmals online veröffentlicht: 21. August 2024